GERAKAN SOSIAL-POLITIK TEMAN AHOK MENJELANG PILKADA DKI JAKARTA TAHUN 2017 - Lubis, Fiero Hutomo; Bandiyah, Bandiyah; Noak, Piers Andreas (Jurnal Nawala Politika, 2019)
ABSTRACT This research aims to know the form of Social-Politic Movement of Teman Ahok towards Province of Jakarta’s Election in 2017. This research uses theoryl of New Social Movement by Nelson A. Pichardo and uses qualitative descriptive method. Sampling technique that is used is purposive sampling. This research shows that the form of Teman Ahok Social-Politic Movement are : first , Teman Ahok arranged a movement called Satu Juta KTP Untuk Ahok to support Ahok for Jakarta’s Election in third quarter of 2015. Teman Ahok was collecting KTP of Jakarta’s people and the target is finished. Second, Teman Ahok uses Social Media to gained peoples who want Ahok to becoming Governor of Jakarta. Third, Teman Ahok was connected with four political parties such as Golkar, Hanura, PSI, and Nasdem while collecting KTP in DKI Jakarta. Every political parties has their own agenda to supported Teman Ahok’s movement. Key Words : Jakarta, Election, Teman Ahok, New Social Movement